AESTHETIC ASPECTS IN ORAL REHABILITATION CORRELATED WITH ACCESS TO NOWADAYS EQUIPMENT - Gabriel G. Condurache; Mădălina Matei; Boancă Andrei Cristian; Buga Vladimir; Kamel Earar (Romanian Journal of Oral Rehabilitation, 2020)
Knowledge of the form, position and the size of the teeth is the key to success in fixed prosthetic restoration. Color is considered most often the most important factor of aesthetic rezult, but a perfect shadow on an incorrect form always leads to a disaster. Some teeth, namely the most prominent ones in the mouth, are of main importance at first sight. Prosthetic restorations of front teeth made by ceramic single tooth in most cases unable to play due to inherent qualities of the materials used, natural appearance and beauty of natural teeth, an impression of vitality, translucency and volume. The maxillary frontal group, due to the privileged position on the maxillary dental arch, represents from an aesthetic point of view a challenge for the dentist when his prosthetic restoration is discussed. The purpose of this study is to individualize the esthetic aspects that govern dental medical practice, in full agreement with the required infrastructure that confers full functionality, beside the compliance with esthetic standards. The transition of both dental medicine cabinets and laboratories towards a digital era confers the premises of achieving of a high degree of performance, both in the field of esthetics and functionality.